Application of Smart Surveillance System in National Security - Suman, Sristi (Unity Journal, 2023)
Surveillance has been considered essential in maintaining order and discipline since the dawn of time. This paper explores various domains revolving around the Smart surveillance system ranging from the primitive definition, and how it deviates from traditional surveillance to how we can implement the system on a fundamental level which can be scaled up to work on national-level systems. With the rising criminal activity in today’s world, there is a need for a proposed solution in surveillance applications that can examine human behavior and recognize people with criminal pasts and detect abnormal activities. This article focuses on proposing advancements in Surveillance Systems in Nepal such that Artificial Intelligence (AI) systems will be able to recognize people with criminal pasts and also keep track of a person's behaviour to predict if any acts of violence are about to take place or not. The research aims to explore the potential for such a system in Nepal and other places around the world, including questions such as: what specific types of AI Surveillance are the governments deploying and “The feasibility and challenges of adopting a Smart Surveillance System in Nepal”. The research methodology consists of secondary sources of data to collect the information. A comparative document study, a quick survey with ICT experts, journal articles, and research on current technologies, found that Nepal is not far behind in technological advancements though it lacks policy-level intervention on AI which shows Nepal can enhance its national security by adopting an AI-powered Surveillance System.